Microbiological analyses for safety and quality assessment of foods and lunch boxes - Pereira, Leandro Tomás (2020)
This report presents the activities and skills acquired during the 10-month curriculum internship at the Microbiology Laboratory of CINATE, Laboratory for food analyses and packaging studies at the Escola Superior de Biotecnologia da Universidade Católica Portuguesa (ESB). This internship allowed the accomplishment of several functions, the most relevant one being the performance of microbiological assays in food, water and surface swab samples, for the detection and quantification of microorganisms indicative of hygiene and contamination conditions. The internship also included maintenance functions of a microbiology laboratory. This internship proved to be enriching and fruitful, as it allowed the development of laboratory and analytical skills in the field of microbiology applied to food safety, sparking my interest for a potential career in this field. In addition, the report also presents concepts of food safety, indicating important foodborne diseases, regulations and regulatory entities of microbiological safety and quality criteria in the food industry. At the same time, a study focusing on the aspects of food safety related to the use of lunch boxes in the transportation of meals was carried out. The use of lunch boxes in the transport of meals has increased, due partly to an increased trend of healthy eating, however, it can become a potential vector of transmission of pathogens if proper maintenance and hygiene practices of lunch boxes are ignored. To evaluate population knowledge on this matter, an online survey was employed as well as an in-person version which was answered simultaneously with evaluation of the microbiological quality of this mode of transportation and storage of meals in which lunch boxes (n=102) of ESB students and staff from the Porto region were analysed. The collected samples were analysed for the count of colony-forming unit (CFU) of Total Viable Count (TVC), Enterobacteriaceae and Escherichia coli hygiene indicators. Pathogen detection of Listeria monocytogenes and Salmonella spp. was also carried out. These parameters were determined using appropriate culture media and biochemical confirmation tests according to procedures of CINATE based on Portuguese and International standards. Salmonella spp. and L. monocytogenes weren’t detected, however, growth of other species of Listeria spp. was detected in 8% (n=8) of the lunch boxes. The results of Total Viable Count and Enterobacteriaceae were compared to limit values established by standards found for food contact surfaces and from this, it was concluded that most of the lunch boxes (59.8%) presented good hygiene conditions according to the obtained low TVC counts. This exploratory study is thusly indicative of the perception and attitude of the population regarding hygiene and food safety practices in the transportation of meals in lunch bags, which in some cases, according to survey results, were inadequate. However, the results of microbiological analysis indicated that hygiene conditions of the analysed bags are mostly acceptable. Greater efforts should therefore be directed towards population information about correct practices to assure food safety during lunch bag use.